The Innovation of Pelayanan Unggulan Pemohon Asing Prioritas (IDE-PUNAPI) at Immigration Office Class I TPI Denpasar - Kadek Tari Septyawati; I Putu Dharmanu Yudharta (West Science Social and Humanities Studies, 2024)
The IDE PUNAPI innovation is a service innovation provided to applicants who are ill to the extent that they cannot walk or are unable to come to the Immigration Office. This innovation aims to provide services to the prioritized foreign applicants who are unable to attend scheduled biometric data collection and interviews and to deliver completed foreign passports with the Residence Permit to the applicants. The purpose of this research is to explore the innovation of Pelayanan Unggulan Pemohon Asing Prioritas (IDE PUNAPI) in Improving Public Services at Immigration Office Class I TPI Denpasar. This study employs a qualitative research method with data analysis techniques, including descriptive analysis and data analysis methods such as data analysis, data reduction, data presentation, and drawing conclusions. The research findings conclude that the IDE PUNAPI public service innovation at Immigration Office Class I TPI Denpasar has been well-implemented. This is evident in the relative advantages demonstrated through the significant advantages of the IDE PUNAPI service innovation received by the public. The update in this research compared to previous studies lies in the research location and the research object, focusing on the service innovation.